Narayanghat-Butwal Road: Delays, Stakeholders Perception, and Completion Stage Risks - K.C., Shambhu; Awasthi, Keshab Datt; Bohara, Niraj (Journal of UTEC Engineering Management, 2025)
This study examines the Narayanghat-Butwal Road: Delays, Stakeholders Perceptions, and Completion Stage Risks. The main causes of delay include poor communication with other stake holder (Forest, Electricity, Nepal Telecom, Irrigation, Ministry of Land Management). Delays in project commencement so that slow administrative mobilization and late site handover further delayed the project start. Due to impact of Covid-19 significantly impacted labour availability, supply chains, and operations. No planning before project starts and unrealistic project schedule bided by the contractor team during bidding also contributed to project delays. Correlation and regression analyses reveal that contractors and consultants strongly influence each other’s perspectives, reflecting close collaboration in fieldwork. In contrast, clients’ perceptions remain more independent, focusing primarily on financial and administrative concerns rather than direct project involvement. This gap affects the overall project coordination and delay management. At the project’s completion stage, key risks were identified including Project budget increase due to price variation, too much pressure to complete the work by contractor, decline in revenue of the country, overall cost increase in the project and loss of confidence of contractor. Hierarchical cluster analysis grouped these risks into three main clusters, escalation and technical delays risks, planning and resource management risk & contractual, legal and economic uncertainty risks.